The influence of birth date and place of development on youth sport participation - Turnnidge, J.; Hancock, D. J.; Côté, J. (Scandinavian Journal of Medicine & Science in Sports, 2014)
Previous research highlights the critical role that contextual factors play in shaping athlete development. The purpose of the present study was to investigate two of these contextual factors: birth date (known as the relative age effect, RAE) and city of development as determinants of participation in a sample of youth ice hockey players. The sample included 146 424 athletes registered with Ontario youth ice hockey between the 2004 and 2010 seasons. Chi-square statistics determined a significant RAE in youth ice hockey. Findings also revealed a significant association between small cities of development and increased youth ice hockey participation. Finally, there was no evidence of an interaction between relative age and city of development. The characteristics of smaller communities that may facilitate sport participation across all youth are discussed, along with recommendations for future research.